Advanced analytical tools in KUKUM's microelectronics laboratory / R. Yusuf …[et al.] - Yusuf, R.; Taking, S.; Halim, N.H.A.; Aris, H.; Hussein, I. (2006)
Advanced analytical tools that have been primarily used for research and development application in the past are now being used extensively to understand semiconductor failure analysis and reliability problems. In this paper, we will discuss an application and technique in the use of Atomic Force Microscopy (AFM), Mini Secondary Ion Mass Spectroscopy (MiniSIMS), and Scanning Electron Microscopy (SEM) for teaching and learning purposes. These tools have been extensively used in identifying semiconductor characterization which contributes to enhancing the fabrication processes in Microelectronic labs specifically.